Bridging Ethnobotany and Islam: Measuring the Feasibility and Practicality of an Ethnobotany Textbook Integrated with Islamic Values - Lia Angela; Muhammad Aflian (Faculty of Tarbiyah and Teacher Training UIN Jurai Siwo, Lampung, 2025)
This study aims to analyze the quality and feasibility of an ethnobotany textbook integrated with Islamic science as an alternative learning resource for students in the Biology Education Study Program. The textbook was developed using the ADDIE model. The developed textbook underwent validation by three experts: a material expert, with a score of 95%; a design expert, with a score of 85,6%; and a language expert, with a score of 93,3%. Practical testing conducted by students and lecturers resulted in an average score of 85.6%, categorizing the textbook as highly practical. The findings indicate that the textbook is both effective and practical to utilize in the learning process. Key strengths of the textbook include its alignment with the lesson plan/course profile and the seamless integration of Islamic science into each section of the textbook.